An Evaluation of the influence of Groundnut Commodity Association membership on the socioeconomic status of women farmers in Mt Darwin district, Zimbabwe - Makuzwa, Fungisayi Susan (BUSE, 2020)
Commodity based associations can effectively transform socioeconomic status of women farmers in women dominated agricultural value chains. Groundnuts being a major crop grown by women in Mt Darwin District of Zimbabwe, profitable production has potential to impact women farmers’ livelihoods. The study evaluated influence of membership to Groundnut Commodity Associations (GCAs) on socioeconomic (SES) status of women farmers. A three-fold approach looking at activities undertaken by GCA and evaluating delivery levels, understanding knowledge gaps and evaluating areas with notable gaps of women member farmers in comparison to non-members and lastly, determining effect of membership to GCA on SES status of the women was used. 175 respondents were purposively sampled (110 members and 65 non-members) from 7 wards with established GCAs. A survey questionnaire was administered. Data was analysed using descriptive statistics, Chi-square tests and Binary logistic regression. Results identified 9 key activities being done at varying degrees, some at 100% such as organizing and registration of farmers and others quite low like dispute resolution at 14%. Members had more knowledge on key groundnut value chain aspects compared to non-members. Knowledge levels varied with highest knowledge at 94% in field practices and lowest on pest and disease management at 59%. Binary logistic regression revealed membership to GCA influenced SES under Education on secondary level only: Members (p=0.045) and non-members (p=0.026), Occupation: Members group: formally employed (p=0.001), informally employed (p=0.004), Self-employed (p=0.001), Not employed (p=0.029), Non-members group: formally employed (p=0.001), informally employed (p=0.011), Marital status: married category only (p=0.024) and Experience: Members with below 5 years (p=0.003), 5 to 10 years (p=0.006), 11-20 years (p=0.0012), Non-members (p= 0.019), (p=0.005) and (p=0.014) respectively. Groundnut Commodity Associations contributed to improving socioeconomic status of women farmers. Optimal implementation of key deliverables can sustainably improve the women’s socio-economic status. Keywords: Groundnut Commodity Associations, Socioeconomic status, Activities, Knowledge gaps
Keywords: Commodity Based Associations; Agricultural value chain